Blind tracking based on Monte Carlo algorithm over MIMO fast time-varying channels - JIANG Ming-yan; YUAN Dong-feng (Tongxin xuebao)
The Monte Carlo algorithm was applied for time-varying channel tracking in communication system and in multi-antenna channels with space time block coding（STBC）.The algorithm was compared with Kalman filtering method under the same condition,the tracking performance was discussed when the system had carrier frequency offset.Simulation results show that the proposed method has good performance in tracking the time-varying channel.